DAMPAK ZAKAT TERHADAP KESEJAHTERAAN MUSTAHIQ BERDASARKAN INDEKS KESEJAHTERAAN BAZNAS (Studi pada Mustahiq Penerima Bantuan Zakat dalam Program Karanganyar Makmur di BAZNAS Kabupaten Karanganyar) - Agustin, Leny (Program Studi Manajemen Zakat dan Wakaf, 2020)
Abstract This study intends to examine the impact of zakat empowerment on the welfare level of mustahik with the main issues are, (1) how is the impact of zakat empowerment on the level of material and spiritual well-being based on the CIBEST Index, (2) how is the impact of zakat empowerment on the level of education and health of mustahiq based on the Human Development Index. , (3) what is the impact of zakat empowerment on the level of independence of mustahiq after receiving zakat assistance based on the Independence Index, (4) how is the impact of zakat empowerment on the welfare of mustahiq in BAZNAS Karanganyar Regency based on the BAZNAS Welfare Index. The purpose of this study was to determine the impact of zakat empowerment on the level of material, spiritual welfare of the mustahiq household, the level of education and health of the mustahiq, recipients of zakat assistance from BAZNAS Karanganyar Regency. The results showed that there was an impact of zakat empowerment on material, spiritual, educational, health and household independence of mustahiq before and after receiving zakat assistance. Based on the BAZNAS Welfare Index, the number of mustahiq households in quadrant I, from 19 to 46, and a decrease in the number of households in quadrant II, from 52 to 25. There were 27 households that experienced an increase in material value. Increase material well-being by 38% and spiritual well-being by 0,5%. The Human Development Index shows a scale of 3, which means that mustahiq are able to get a good education and health. Independence Index after receiving the zakat empowerment program which shows a scale of 4 which is strong. Abstrak Penelitian ini bermaksud mengkaji dampak pemberdayaan zakat terhadap kesejahteraan mustahiq dengan pokok permasalahan adalah, (1) bagaimana dampak pemberdayaan zakat terhadap tingkat kesejahteraan material dan spiritual berdasarkan Indeks CIBEST, (2) bagaimana dampak pemberdayaan zakat terhadap tingkat pendidikan dan kesehatan mustahiq berdasarkan Indeks Pembangunan Manusia, (3) bagaimana dampak pemberdayaan zakat terhadap tingkat kemandirian mustahiq pasca menerima bantuan zakat berdasarkan Indeks Kemandirian, (4) bagaimana dampak pemberdayaan zakat terhadap kesejahteraan mustahiq di BAZNAS Kabupaten Karanganyar berdasarkan Indeks Kesejahteraan BAZNAS. Tujuan penelitian ini adalah untuk mengetahui dampakpemberdayaan zakat terhadap tingkat kesejahteraan material, spiritual rumah tangga mustahiq, tingkat pendidikan dan kesehatan mustahiq, penerima bantuan zakat BAZNAS Kabupaten Karanganyar. Hasil penelitian menunjukkan adanya dampak dari pemberdayaan zakat terhadap kesejahteraan material,spiritual, pendidikan, kesehatan, dan kemandirian rumah tangga mustahiq sebelum dan sesudah menerima bantuan zakat. Berdasarkan Indeks Kesejahteraan BAZNAS, jumlah rumah tangga mustahiq pada kaudran I yang semula 19 menjadi 46 rumah tangga dan terjadi penurunan jumlah rumah tangga pada kuadran II yang semula 52 rumah tangga menjadi 25 rumah tangga. Terdapat 27 rumah tangga yang mengalami kenaikan secara material value. Terjadi peningkatan kesejahteraan material sebesar 38% dan kesejahteraan spiritual 0,5%. Indeks Pembangunan Manusia menunjukkan skala 3 yang artinya mustahiq mampu memperoleh pendidikan dan kesehatan dengan baik. Indeks Kemandirian pasca menerima program pemberdayaan zakat yang menunjukkan skala 4 yaitu kuat.